Nanomedicine for Cystic Fibrosis. (April 2019) - Ong, Victor; Mei, Vincent; Cao, Lin; Lee, Kiana; Chung, Eun Ji
Cystic fibrosis is a genetic disease affecting more than 70, 000 people worldwide. Caused by a mutation in the CFTR gene, cystic fibrosis can result in difficulty breathing, widespread bacterial infections, edema, malnutrition, pancreatitis, and death. Current drug-based treatments struggle to reach the site of action due to the thick mucus, and only manage symptoms such as blocked airways, lung infections, and limited ability to digest food. Nanotechnology opens up possibilities for improved treatment strategies by focusing on drug penetration through the mucus lining, eliminating resulting bacterial infections, and targeting the underlying genetic cause of the disease. In this review, we present recent nanoparticle developments for cystic fibrosis, challenges in nanomedicine therapeutics, and future research directions in gene editing and nonviral vectors for gene delivery.